YUKARI FIRAT BÖLGESİ'NDE MULTİPL SKLEROZ TANISI İLE İZLENEN HASTALARIN EPİDEMİYOLOJİK, DEMOGRAFİK ÖZELLİKLERİ VE AİLESEL SIKLIĞI - KILIÇ, ERSİN (Fırat Üniveristesi, 2017)
Bizim çalışmamızda; multipl sklerozlu hastaların başlangıç yaşları ve yakınmalarını, klinik alt tiplerinin sıklığını, hastalığın takipleri boyunca her bir klinik alt tipinde nasıl seyrettiğini, bu klinik alt tipler arasındaki farklılıkları göstermeyi, hastalar arasındaki ailesel sıklığı, Vizuel uyarılmış potansiyeller (VEP) ve Oligoklonalband (OKB) sonuçlarını belirlemek amaçlandı. Çalışmaya Yukarı Fırat bölgesinde (Elazığ, Tunceli, Bingöl, Muş illeri ağırlıklı olmak üzere) ikamet eden gözden geçirilmiş, McDonald tanı kriterine göre kesin multipl skleroz (MS) tanısı almış dosyaları eksiksiz olan hastalar dâhil edildi. Demografik ve vaka ile ilgili bilgiler Fırat Üniversitesi Tıp Fakültesi Nöroloji AD'nın veritabanından kaydedildi. Fırat Üniversitesi Tıp Fakültesi Nöroloji Kliniği'nde takip edilen 257 Multipl skleroz hastası çalışmaya alındı. Hastaların %31.9'i erkek, %68.1'i kadın olarak bulundu. Kadın erkek oranı 2.13/1 ortalama başlangıç yaşı 31.90±9.6, erkeklerde 31.94±9.6, kadınlarda 31.89±9.2 olarak bulundu. Çalışmada en sık başlangıç semptomlarını sensoriyel ve motor bulguların oluşturduğu gözlendi. Hastalığın klinik seyri %72.37 relapsing remitting multipl skleroz, %19.07 sekonder progresif multipl skleroz, %4.28 primer progresif multipl skleroz ve %4.28 benign multipl skleroz olarak belirlendi. Ailesel MS sıklığı %8,9 olarak kaydedildi. Hastaların %22,6'sında VEP normal, %77,4'ünde VEP uzamış olarak tespit edildi. Hastaların %96.1'inde OKB pozitif, %3.9'unda ise OKB negatif olarak tespit edildi. Bu çalışmanın sonucunda Yukarı Fırat Bölgesi'nde MS'in en sık kadınlarda görüldüğü, en sık 20-40 yaşlar arasında başladığı, en sık görülen tipinin RRMS olduğu, en sık duyusal ve motor bulgularla başladığı sonucuna varıldı. Anahtar Kelimeler: Multipl skleroz, Yukarı Fırat Bölgesi, epidemiyoloji, genişletilmiş özürlülük durum skalası

The aim of the present study was to reveal age and symptoms at disease onset in patients with MS, frequency of individual clinical subtypes and their clinical courses during the follow-up of patients, and the differences between these clinical subtypes, and establish familial frequency and the outcomes of visual evoked potentials (VEPs) and oligoclonal band (OCB) positivity. The study included patients residing in the Upper Euphrates Section (mainly the provinces of Elazığ, Tunceli, Bingöl, Muş) who were diagnosed with MS according to the revised McDonald criteria and who had complete medical records. Demographic data and data about the cases were retrieved from the database of Firat University, Faculty of Medicine, Department of Neurology. A total of 257 patients with MS, who were followed at Firat University, Faculty of Medicine, Department of Neurology were included in the study. Of these patients, 31.9% were males and 68.1% were females. Female-to-male ratio was 2.13/1, the mean age at disease onset was 31.90±9.6 years in whole group, 31.94±9.6 years in males, and 31.89±9.2 in females. Sensorial and motor symptoms comprised the majority of the initial presenting symptoms. The clinical course was characterized by relapsing-remitting MS (RRMS) in 72.37%, secondary progressive MS (SPMS) in 19.07%, primary progressive MS (PPMS) in 4.28%, and benign MS (BMS) in 4.28% of the patients. The incidence of familial MS was 8.9%. In addition, VEPs were normal in 22.6% of the patients, whereas 77.4% had prolonged VEPs. OCBs were positive in 96.1% of the patients and negative in 3.9% of the patients. Our study results show that MS most commonly affects women aged between 20 and 40 years in the Upper Euphrates Section, and the most common type of MS is RRMS which typically starts motor and sensorial manifestations. Keywords: Multiple sclerosis, Upper Euphrates Section, epidemiology, Expanded Disability Status Scale.
Epidemiological, demographical features and familial frecuency of the patients with multi?ple sclerosis followed in upper euphrates section
Keywords: Nöroloji